Recent advances in liquefaction technologies for production of liquid hydrocarbon fuels from biomass and carbonaceous wastes. (November 2019) - Perkins, Greg; Batalha, Nuno; Kumar, Adarsh; Bhaskar, Thallada; Konarova, Muxina
Abstract: The liquefaction of biomass and carbonaceous wastes using hydro-pyrolysis, hydrothermal liquefaction or liquefaction using water and hydrocarbon solvents are promising thermochemical methods for producing renewable fuels and chemicals. New combinations of unit operations and possibly novel reactors will likely be required to economically convert biomass feedstock into partially upgraded bio-crudes. While some techno-economic assessments show that biofuels from fast pyrolysis may be competitive with petroleum fuels in future, conventional pyrolysis produces a poor quality bio-crude and is only suitable for dry, homogenous feedstock such as woody biomass, agricultural waste (corn stoves, wheat stalk, and rice husk). It is desirable to produce high-quality bio-crudes and to be able to process high-moisture feedstock such as algae, organic waste (food residues), bio-solids and bio-sludge into transportation fuels using the liquefaction approaches. Increased awareness of the environmental damage from burning fossil fuels is driving national and international reduction targets for on CO2 emissions. Liquefaction technologies aimed at producing alternatives to fossil-based transportation fuels/hydrocarbons are likely to receive continued support in the future and the most promising ones could be developed to full commercial scale. This review provides a summary of the current state of development of these technologies and also some of the challenges faced to develop commercially viable transportation fuels via liquefaction routes. This review compares liquefaction routes and provides a summary of techno-economic analyses where data is available and discusses the challenges and opportunities associated with commercial scale-up. Highlights: Review of hydropyrolysis and hydrothermal liquefaction. Review of liquefaction in hydrocarbon solvents. Summary of process development status. Comparison of process performance, economics and technology readiness.